Exploring Algorithmic Solutions for Effective Decisions Concerning Investments in Equity Stocks Amidst Financial Disruptions Using the COVID 19 and Sub-prime Crises as Case Studies - Shaunak Mainkar; Hemangi Borawake; Tanishq Ranjane (Australasian Accounting, Business and Finance Journal, 2024)
Investors face a basic dilemma during a financial crisis i.e., whether to exit and re-enter or to continue with the existing set of positions. The timing of entry and exit plays a crucial role in determining the rate of returns generated by a portfolio. Thus, the problem faced by investors during a crisis is whether to exit or to continue and how to determine the timing of exit if the first option is chosen. This research paper attempts to find solutions to the problems faced by investors. The research paper focuses on addressing the parameters used to determine the exit and re-entry and the time factor associated with it. A timely entry in the right stocks will lead to a good return on the portfolio. The research paper is an attempt to determine the factor by which rate of return is affected if the norms of timely entry and exit are followed. The team of researchers has identified two specific times in the history of financial markets when the fall in the markets was considerable and led to a lot of confusion amongst investors. These two times are the case studies for comparison: The first one is the sub-prime lending crisis in 2008-09 and the second one is the fall due to COVID-19 in 2019-20. These two events underline the fact that decision making in the financial markets is a very subjective domain and the returns are dependent on the system followed by the investors.
Keywords: Financial crisis; investment; sub-prime crisis; COVID-19; portfolio